KEBUTUHAN BELAJAR MASYARAKAT DI DESA BUMBUNG KECAMATAN MANDAU KABUPATEN BENGKALIS - Natuna, Daeng Ayub (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research aims to determine how high the level of Community Learning Needs. Benefits of this academic research is as a scientific work that can enhance the development of science, especially for non-formal education in formulating learning needs in accordance with the needs of society. Practical and is as a positive outcome for the government in making policies and programs that can improve education and the economy in accordance with the needs of society. This type of research is descriptive using a quantitative approach which aims to provide a systematic overview of the state of the object under study. Data collection techniques in this research is through observation, interview and questionnaire. All statements in the questionnaire or questionnaires presented in the form of Likert scale adapted to the statement. Place this research was conducted in the village Bumbung Mandau subdistric Bengkalis regency. This study was conducted over a span of a month of October 2014 until May 2015. The population in this study were people aged 18- 47 years, amounting to 3,973 people and for the sample was 199 people. Recapitulation learning needs of people in rural districts tube Mandau Bengkalis district in the review of the indicators needs to learn at the age of 18-47 years overall mean value of 3.75 was obtained and included into high category or priority. The results of recapitulation when viewed from each sub-indicator on the age category of 18-47 years from the highest to lowest are: 1) The need for learning related to religious 4.07 and can be categorized as very high or very priorities. 2) Requirements relating to personal appearance Mean values obtained 4.02 and can be categorized as very high or very priorities. 3) The need for learning associated with household Mean values obtained 3.90 and can be categorized as high or priority. 4) The need for learning related to the business acquired in agriculture Mean values of 3.86 and can be categorized as high or priority. 5) The need for learning associated with the newly acquired knowledge of tourism Mean values of 3.76 and can be categorized as high priority. 6) The need for learning related to language acquisition and general knowledge acquired Mean values of 3.67 and can be categorized as high or priority. 7) The need for learning related to the job duties Mean values obtained 3.66 and can be categorized as high or priority. 8) The need for learning associated with indulgence and recreation Mean values obtained 3,63 and can be categorized as high priority. 9) The need for learning related to services obtained Mean values of 3.17 and can be categorized as high or priority.